A comparative analysis of condom use among unmarried youths in rural community in Nigeria (2011)
Globally, youths are more sexually active than any subgroup of the population. In Nigeria, the prevalence of condom use among youths is low. This study explored and compared condom use among in-school youths and out-of-school youths in south western Nigeria. This population based study used multistage random sampling technique to select eligible 600 youths aged 15-24 years which included 300 high school students and 300 out-of-school youths in Ekiti West Local Government area of Ekiti state, Nigeria. Descriptive statistics, t-test, chi square test and logistic regression were used for analysis. The mean age of in-school youths and out of school youths were 18.1±2.2 years and 19.0±2.7 years respectively. Overall, 35.5% of all sexually active respondents, 29.8% in-school and 40.8% out-of-school youths reported to have ever used condom during sexual intercourse (p<0.05) The study concluded that although, condom use is low across the study population, but higher among out-of-school youths. Youths aged 15-24 should be given free access to condom particularly the in-school youths.